FLT3 mutation and expression did not adversely affect clinical outcome of childhood acute leukaemiaua study of 531 Southeast Asian children by the Ma-Spore study group - Leow, S.; Kham, S.Kow-Yin; Ariffin, H.; Quah, T.C.; Yeoh, A.Eng-Juh (John Wiley & Sons, 2010)
FMS-like tyrosine kinase 3 (FLT3) is critical for normal haematopoiesis and have been reported to be expressed in the majority of acute myeloid and lymphoid malignancies. We correlated the impact of FLT3 mutations and its expression with age, WHO 2008 classification and treatment outcome in 531 childhood acute leukaemias. Of 150 acute myeloid leukaemia (AMLs), 18 (12%) harboured FLT3-ITD while nine (6%) had FLT3-TKD. FLT3-ITD and -TKD were rare in acute megakaryoblastic leukaemia (AMKL; FLT3-ITD 0/26, FLT3-TKD 1/26) and children below 3years (n=2/48). Acute promyelocytic leukaemia (APL) with t(15;17);PML-RARa (n=7/18; 39%) harboured the highest frequency of FLT3 mutations, followed by myelomonocytic (n=4/18; 22%) and AML with t(8;21);RUNX1-RUNX1T1 (n=2/21; 9%). FLT3 expression levels were also lowest in AMKL, both in Down's and non-Down's (p=0.002) followed by patients <3years (p=0.001). The rarity of FLT3 mutations and expression levels in AMKL were independent of age. Conversely, only 2% of childhood acute lymphoblastic leukaemia (ALL) harboured FLT3 mutations (ITD=1/381; TKD=6/381). FLT3 was highly expressed in hyperdiploid ALL (p<0.001). Of the 121 AMLs with clinical history, there were no significant differences in 4-year event-free survival (EFS) (46% vs. 38%; p=0.46) and overall-survival (OS) (55% vs. 43%; p=0.30) between FLT3-wildtype and ITD+ patients. Similarly, FLT3 expression levels did not influence survival in AML in both the good risk and non-good risk subgroups. FLT3 does not appear to be involved in the pathogenesis of AMKL, both in Down's and non-Down's. Therapeutic targets using FLT3 inhibitors may not be useful in AMKL and in young children with AML. Copyright (C) 2011 John Wiley & Sons, Ltd.